Hyperhomocysteinemia predicts renal function decline: a prospective study in hypertensive adults - Xie, Di (Sci Rep, 2015)
Hyper-homocysteinemia (HHcy) is associated with microalbuminuria and glomerular injury in general and diabetic populations. However, HHcy’s role in hypertensive patients was not studied. We investigated whether HHcy is an independent risk factor for renal function decline and development of chronic kidney disease (CKD) in hypertensive men and women. This was a community-based prospective cohort study of 2,387 hypertensive adults without CKD at baseline, with a mean follow-up of 4.4 years. Baseline and follow-up levels of plasma Hcy, folate, vitamin B12, blood pressure and other pertinent covariables were obtained. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/per 1.73 m(2) and an eGFR decline rate >1 ml/min/per 1.73 m(2)/year. There was a graded association between Hcy tertiles and eGFR decline. Subjects in the 3(rd) tertile of Hcy levels had an accelerated rate of eGFR decline and an increased risk of incident CKD, as compared with those in the 1st tertile, after adjusting for age, gender, baseline diabetes, SBP, BMI, smoking, dyslipidemia, eGFR, folate and vitamin B12 levels. In conclusion, in this prospective cohort of Chinese hypertensive adults, elevated baseline plasma Hcy can serve as an independent biomarker to predict renal function decline and incident CKD.